2009
DOI: 10.1063/1.3253685
|View full text |Cite
|
Sign up to set email alerts
|

Direct determination of the Tolman length from the bulk pressures of liquid drops via molecular dynamics simulations

Abstract: An expression for the difference in pressure between a liquid drop in equilibrium with its vapor ⌬p = p ᐉ − p v is derived from previous expressions for the components of the Irving-Kirkwood pressure tensor. This expression, as well as the bulk values of the pressure tensor, is then evaluated via molecular dynamics simulations of particles interacting through a truncated Lennard-Jones potential. We determine the Tolman length ␦ from the dependence of ⌬p on the equimolar radius. We determine the Tolman length t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
98
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(121 citation statements)
references
References 26 publications
(37 reference statements)
18
98
1
2
Order By: Relevance
“…Subsequent studies, however, have also found δ to be negligible or even equal to zero [20,63,76], positive and larger than σ [25,66], negative with −σ < δ < 0 [22,24,77] or negative and diverging (δ 0 = −∞) in the planar limit [78], while others have claimed that the sign of δ is curvature dependent itself [79,80]. Thereby, they have only proven the mutual inconsistency of their assumptions and methods, while nothing is truely known about δ and the dependence of the surface tension on curvature.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequent studies, however, have also found δ to be negligible or even equal to zero [20,63,76], positive and larger than σ [25,66], negative with −σ < δ < 0 [22,24,77] or negative and diverging (δ 0 = −∞) in the planar limit [78], while others have claimed that the sign of δ is curvature dependent itself [79,80]. Thereby, they have only proven the mutual inconsistency of their assumptions and methods, while nothing is truely known about δ and the dependence of the surface tension on curvature.…”
Section: Discussionmentioning
confidence: 99%
“…The most widespread implementation of this approach in terms of intermolecular pair potentials makes use of the Irving-Kirkwood (IK) [43] pressure tensor, which was first applied to (spherical) interfaces by Buff [13] and underlies the simulation studies of Vrabec et al [25] as well as those of van Giessen and Blokhuis [24]. Its normal component is given by [34,43] …”
Section: B the Mechanical Routementioning
confidence: 99%
See 3 more Smart Citations